Pengembangan Perangkat Middleware Web of Things (WoT) Berbasis Arsitektur Publish Subscribe Menggunakan Protokol REST HTTP - Donny Kurniawan; Adhitya Bhawiyuga; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet of Things (IoT) refers to all physical objects or devices that connect and exchange data over the Internet. With the application of IoT in various fields, of course cannot be separated from the increasing challenge also. One of the major problems in IOT deployment includes devices with diverse protocols and accessibility of various devices. One solution that can be given to solving interoperability problems is to use the web as a universal integration platform. However, the application of WoT in sending commands to IoT devices becomes inefficient because the IoT device makes periodic requests as a command check mechanism. Therefore, it is necessary to replace the more efficient architecture in overcoming the delivery of middleware commands to the sensor nodes. To overcome the problem is required replacement HTTP RESTful request response architecture to use publish subscribe architecture. Based on the previous explanation, it is proposed a middleware development with publish subscribe architecture as communication of sensor node device to middleware. In replacement of the architecture is expected to reduce the load from the IoT device, so no need to make requests on a regular basis. System performance test results show, the system capable of handling up to 150 users with a 0% error rate.